Effects of Maturation Stage on Physical Fitness in Youth Male Team Sports Players After Plyometric Training: A Systematic Review and Meta-Analysis - Gesheng Lin; Jiayong Chen; Ruixiang Yan; Beiwang Deng; Wenfeng Song; Bo Guan; Jian Sun (Sports Medicine - Open)
Abstract Background Plyometric training (PT) is widely used to enhance physical fitness in youth team sport athletes, but its effects may vary across maturation stages due to developmental differences. This study aimed to comprehensively evaluate the impact of PT on multiple physical fitness outcomes across different maturation stages in youth male team sport athletes. Methods A systematic search was conducted in PubMed, Web of Science, Scopus, and SPORTDiscus. Included studies were randomized controlled trials involving male youth team sport athletes (10–18 years) who underwent ≥ 4 weeks of bodyweight plyometric training compared to active controls, with outcomes related to physical fitness. Methodological quality was assessed using the PEDro scale. Effect sizes (Hedges’g) were calculated using a random-effects model with 95% confidence intervals and prediction intervals (PI). Egger’s test and the trim-and-fill method were used to assess and adjust for publication bias. Subgroup analyses explored training-related moderators. Results A total of 36 studies were included, involving 663 soccer players, 230 basketball players, 54 handball players, and 110 volleyball players. PT significantly improved CMJ in the overall group (ES = 0.74, 95% PI [− 0.29 to 1.78]) and in PRE (ES = 0.83, 95% PI [− 0.93 to 2.58]), MID (ES = 0.50, 95% PI [0.27 to 0.73]), and POST (ES = 1.05, 95% PI [− 0.25 to 2.35]). SLJ improved in the overall group (ES = 0.52, 95% PI [0.30 to 0.74]), PRE (ES = 0.53, 95% PI [0.21 to 0.85]), and POST (ES = 0.87, 95% PI [− 1.06 to 2.81]), but not in MID (P > 0.05). ≤ 10 m sprint improved in the overall group (ES = − 0.58, 95% PI [− 1.45 to 0.30]), PRE (ES = − 0.43, 95% PI [− 0.85 to − 0.02]), and POST (ES = − 1.31, 95% PI [− 2.66 to 0.04]), but not in MID (P > 0.05). > 10 m sprint improved in all groups: overall (ES = − 0.41, 95% PI [− 0.91 to 0.09]), PRE (ES = − 0.28, 95% PI [− 0.54 to − 0.01]), MID (ES = − 0.32, 95% PI [− 0.57 to − 0.07]), and POST (ES = − 1.16, 95% PI [− 3.38 to 1.05]). COD improved in the overall group (ES = − 0.84, 95% PI [− 1.76 to 0.08]), PRE (ES = − 0.80, 95% PI [− 1.89 to 0.29]), MID (ES = − 0.59, 95% PI [− 1.01 to − 0.17]), and POST (ES = − 1.52, 95% PI [− 3.10 to 0.05]). PT showed no significant effect on maximal dynamic strength (P > 0.05). Subgroup analyses showed that ≥ 16 PT sessions led to greater improvements in CMJ (ES = 1.08 vs. 0.35) and COD (ES = − 1.05 vs. − 0.59) performance in the overall group, and in CMJ in the POST stage (ES = 1.64 vs. 0.54), compared to ≤ 14 sessions. CMJ gains were also greater with ≥ 8 week interventions than with ≤ 7 weeks (ES = 1.00 vs. 0.43). Conclusion PT effectively improves physical fitness in youth male team sport athletes, except for maximal dynamic strength. The greatest gains were observed in the POST stage, while the MID stage showed the smallest gains in jump and COD, with no significant effects observed for SLJ and ≤ 10 m sprint. The ranges of all prediction intervals suggest a higher likelihood of positive effects in future studies. Considering that some prediction intervals were relatively wide and crossed zero, further research is needed to better identify and manage the variability in training adaptations, particularly during the POST stage. Additionally, PT programs with at least 16 sessions or lasting 8 weeks appear to be more effective.